Rebar corrosion modelling and deterioration limit state - Andrade Perdix, Carmen (Revista ALCONPAT, 2020)
In present work the limitations of the models of corrosion initiation with indications to overcome them, are presented. Performance based design of durability is at present a trend considered in FIB Model Code (MC2010). However, we are still far from accurately predicting the performance of a structure in a specific environment, in spite of which performance-based requirements are introduced in the concrete specifications of large infrastructures demanding 100 years or more of service life. Also are commented the depassivation step and the propagation period with considerations on their probabilistic treatment. It is proposed to consider corrosion onset as a “deterioration or initiation Limit State” (DLS or ILS). An example of calculation the time to cover-cracking induced corrosion is included.